1997
DOI: 10.1093/genetics/147.4.1743
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Male-Specific Lethal-4 Protein: Structure/Function Analysis and Dependence on MSL-1 for Chromosome Association

Abstract: MSL-2 is required for the male-specific assembly of a dosage compensation regulatory complex on the X chromosome of Drosophila melanogaster. We found that MSL-2 binds in a reproducible, partial pattern to the male Xchromosome in the absence of MLE or MSL-3, or when ectopically expressed at a low level in females. Moreover, the pattern of MSL-2 binding corresponds precisely in each case to that of MSL-1, suggesting that the two proteins function together to associate with the X. Consistent with this hypothesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(33 citation statements)
references
References 0 publications
1
28
0
2
Order By: Relevance
“…In previous work, we compared the binding sites for partial MSL complexes that lacked either the Msl3 protein or the Mle helicase [14]. The two different kinds of incomplete complexes bound nearly identical sets of chromatin entry sites in msl3 and mle mutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we compared the binding sites for partial MSL complexes that lacked either the Msl3 protein or the Mle helicase [14]. The two different kinds of incomplete complexes bound nearly identical sets of chromatin entry sites in msl3 and mle mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type males have complete MSL complexes bound to hundreds of bands along the X chromosome in a highly reproducible pattern where they mediate hypertranscription. Genetic analysis of debilitated MSL complexes lacking either Mle, Msl3 or Mof subunits, or containing enzymatically dead Mof acetyltransferase or Mle helicase, has shown that partial MSL complexes can bind to only ~35 bands, named chromatin entry sites (formerly called high-affinity sites [9,[13][14][15][16]). Recently, we proposed that these sites direct dosage compensation to the X chromosome by serving as sites of assembly and subsequent spreading of the MSL complex into flanking chromatin in cis [9].…”
Section: Epigenetic Spreading Of Msl Complexes From a Rox2 Transgene Into Flanking Chromatinmentioning
confidence: 99%
“…2 The MSL and MSL2 proteins are both essential for binding of the complex to the high affinity sites. 22 These proteins form a complex via their respective amino terminal domains. 23,24 A basic motif within the amino terminal domain of MSL is essential for the MSL/MSL2 complex to bind to high affinity sites on the X chromosome but was not required for interaction with MSL2.…”
Section: Point Of Viewmentioning
confidence: 99%
“…Targeting of the components of the dosage compensation complex, including MOF, to the Drosophila male X chromosome is thought to occur stepwise, with initial recruitment mediated by the MSL1 and MSL2 proteins. This protein pair recognizes a limited number of sites on the X chromosome (Lyman et al, 1997), which may contain short and degenerate DNA sequence motifs that help to distinguish the X chromosome from autosomes (Gilfillan et al, 2007). MOF may make its way to these sites of initial binding through interactions with MSL1 and MSL3 (Straub and Becker, 2007).…”
Section: Chromatin Proteins Do Double Dutymentioning
confidence: 99%